How (i)rrational are we? A case of Croatian inflation - Nataša Erjavec; Ivana Lolić; Petar Sorić (Croatian Operational Research Review, 2015)
This paper examines the validity of the rational expectations hypothesis (REH) in the case of Croatian consumers and their inflation estimates. The added value of this paper in comparison to previous similar studies lies in the state space methodology, allowing the authors to test for potential time variability of the estimated relationship between actual and expected inflation. The obtained results can be summarized as follows: i) consumers heavily over-estimated actual inflation throughout the entire period 2005-2014, leading to the rejection of the REH; ii) consumer bias against inflation intensifies in times of abrupt price hikes (2007 and 2008), and diminishes in times of lower inflation volatility (2014). This empirical rejection of the REH is in line with previous research on the topic, providing additional evidence that the theoretical paradigm of homo economicus is heavily flawed.